Sei sulla pagina 1di 3

Notes — Introduction to probability.

March 15, 2019


1 Probability and counting
Definition 1. Sample space and event
The sample space S of an experiment is a set of all possible outcomes
of that experiment. An event A is a subset o sample space S, and we
say that A occurred it the actual outcome is A.
Definition 2. Naive definition of probability
Let A be an event for an experiment with a finite sample space S. The
naive probability of A is
card(A) number of outcomes favorable to A
Pnaive (A) = =
card S total number of outcomes
Theorem 1. Multiplication rule
If we have experiment A, B with possible outcomes a, b then the com-
pound experiment has a ∗ b possible outcomes.
Proof. Imagine a forest with a trees having b children.
Definition 3. Formal definition of probability (axioms of probability)
Given set Ω and a function

P : P(Ω) → [0, 1]

following must hold:


1. P (∅) = 0
2. P (Ω) = 1
3. If A is countable family of disjoint sets:
∞ ∞
!
[ X
P Ai = P (Ai )
i=0 i=0

Theorem 2. Basic properties


1. P (Ac ) = 1 − P (A)
2. If A ⊆ B then P (A) ≤ P (B)
3. P (A ∪ B) = P (A) + P (B) − P (A ∪ B)
Proof. 1. It follows from the following observation.

1 = P (Ω) = P (A ∪ Ac ) = P (A) + P (Ac )

2.
P (B) = P ((B \ A) ∪ A) = P (B \ A) + P (A)
Since P (B \ A) ≥ 0, thesis follows.

1
3.
P (A ∪ B) = P (A ∪ (B ∩ Ac )) = P (A) + P (B ∩ Ac )
Now:

P (A ∩ B) + P (Ac ∩ B) = P ((A ∩ B) ∪ (Ac ∩ B)) = P (B)

Thesis follows by elementary “algebra”.

Definition 4. Independent events


If A is a family of sets, then we say that the sets are independent iff:
For all B ⊆ A and B is finite, we have:
n
! n
\ Y
P Bi = P (Bi )
i=0 i=0

Definition 5. Conditional probability


If A, B are event and P (B) > 0 then

P (A ∩ B)
P (A | B) =
P (B)

Intuition about this definition can be following: The event we are in-
1
terested in is A ∩ B in restricted universe, scaled by P (B) .

Lemma 1. We observe that from the definition of conditional proba-


bility:
P (A ∩ B) = P (B | A)P (B) = P (A|B)P (A)
Theorem 3. Bayes theorem

P (B | A)P (A)
P (A | B) =
P (B)

Proof. Follows immediately from the lemma.

1.1 Exercises